PENGARUH LATIHAN NEURO DEVELOPMENTAL TREATMENT (NDT) TERHADAP TONUS OTOT DAN KEMAMPUAN MOTORIK PADA ANAK DOWN SYNDROME - Rusdiyah Nur Imani; Dwi Agustina; Andy Martahan Andreas Hariandja (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Background: Down syndrome is a condition in which a child has an extra triple of chromosomes or trisomy of all or part of chromosome 21 which causes impairment in brain growth and development. Purpose: This study was to determine the effect of Neuro-Developmental Treatment (NDT) exercise on muscle tone and motor skills in children with Down syndrome. Methods: The research design in this study was pre-experimental. This study used secondary data from medical records at KKTK and IRM in the physiotherapy section of Harapan Kita Hospital from January 2017 to December 2020 with a sample size of 15 respondents who were selected using quota sampling. The independent variable was NDT, and the dependent variable, muscle tone was measured by Asworth and motor skills by GMFM. Data collection techniques was medical record documentation. Results: The average muscle tone increased significantly by about 0.86 from 0.67 to 1.06 with a P value of 0.000. Motoric ability also experienced a significant increase of 55.93 from 10.01 to 65.94. Conclusion: In children with Down syndrome, muscle tone and motor skills experience correlated disorders, so these two aspects must be considered when carrying out physiotherapy. NDT is an effective therapy in increasing muscle tone and motor skills in children with Down syndrome.